Modulation of Ca(2+) oscillation and melatonin secretion by BK(Ca) channel activity in rat pinealocytes - Mizutani, Hiroya (Am J Physiol Cell Physiol, 2016)
The pineal glands regulate circadian rhythm through the synthesis and secretion of melatonin. The stimulation of nicotinic acetylcholine receptor due to parasympathetic nerve activity causes an increase in intracellular Ca(2+) concentration and eventually downregulates melatonin production. Our previous report shows that rat pinealocytes have spontaneous and nicotine-induced Ca(2+) oscillations that are evoked by membrane depolarization followed by Ca(2+) influx through voltage-dependent Ca(2+) channels (VDCCs). These Ca(2+) oscillations are supposed to contribute to the inhibitory mechanism of melatonin secretion. Here we examined the involvement of large-conductance Ca(2+)-activated K(+) (BK(Ca)) channel conductance on the regulation of Ca(2+) oscillation and melatonin production in rat pinealocytes. Spontaneous Ca(2+) oscillations were markedly enhanced by BK(Ca) channel blockers (1 μM paxilline or 100 nM iberiotoxin). Nicotine (100 μM)-induced Ca(2+) oscillations were also augmented by paxilline. In contrast, spontaneous Ca(2+) oscillations were abolished by BK(Ca) channel opener [3 μM 12,14-dichlorodehydroabietic acid (diCl-DHAA)]. Under whole cell voltage-clamp configurations, depolarization-elicited outward currents were significantly activated by diCl-DHAA and blocked by paxilline. Expression analyses revealed that the α and β3 subunits of BK(Ca) channel were highly expressed in rat pinealocytes. Importantly, the activity of BK(Ca) channels modulated melatonin secretion from whole pineal gland of the rat. Taken together, BK(Ca) channel activation attenuates these Ca(2+) oscillations due to depolarization-synchronized Ca(2+) influx through VDCCs and results in a recovery of reduced melatonin secretion during parasympathetic nerve activity. BK(Ca) channels may play a physiological role for melatonin production via a negative-feedback mechanism.